A retrospective study on the prevalence of oral cancer among smoking patients examined at the Philippine General Hospital from the years 1979-1989 - Amigo, Josephine Ann
In this study, records from the Philippine General Hospital-Pathology Department were examined and data were gathered regarding the incidence and the prevalence of oral cancer among Filipinos (includes the tongue, buccal mucosa, palate, gingiva, lip, floor of the mouth and the cheeks) who smoked constantly. Data gathered were than subjected to statistical analysis. Results showed that among Filipino smokers, oral cancer had a significant prevalence.